A Phenomenological Study of Three University Students’ Experiences in Project Based Learning - Yustinus Calvin Gai Mali (JEELS (Journal of English Education and Linguistics Studies), 2016)
Researchers in the past have explored practices of Project Based Learning (PBL) in various educational contexts. Nevertheless, previous studies that examine project-based learning in English as a Foreign Language (EFL) contexts are still limited in numbers particularly through the eyes of Indonesian university students. This study aims to look into meanings of PBL in learning Second Language Acquisition (SLA) at English Language Education Program, Dunia University Indonesia. The study specifically described how three students in the class felt about PBL as implemented in two main classroom projects, how they experienced doing it, and how they provided meaning to it. The students’ experiences were recalled through an in-depth phenomenological interview. The results of the study were the experiences in the form of narratives and my interpretation of emerging themes in the narratives as the meanings of PBL in learning SLA. The study appeared to continue positive trends of PBL practices in English language teaching and learning specifically in contentbased instructions.